How does it feel to be part of the minority? Impacts of perspective taking on prosocial behavior - Marisol Rodríguez Chatruc; Sandra V. Rozo (Inter-American Development Bank (IDB), 2021)
Can taking the perspective of an out-group reduce prejudice and promote prosociality? Building on insights from social psychology, we study the case of Colombian natives and Venezuelan immigrants. We conducted an online experiment in which we randomly assigned natives to either play an online game that immersed them in the life of a Venezuelan migrant or to watch a documentary about Venezuelans crossing the border on foot. Relative to a control group, both treatments increased altruism towards Venezuelans and improved some attitudes, but only the game significantly increased self-reported trust.
Keywords: C91; D91; J15; 330; migration; prejudice; perspective taking; altruism; trust